PENGARUH PENGALAMAN KERJA DAN TINGKAT PENDIDIKAN TERHADAP KINERJA PETUGAS PELAYANAN KESEHATAN DI RSUD Dr. SLAMET MARTODHIRDJO KABUPATEN PAMEKASAN - Indah Sukma Poniandari; Nugroho Mardi W; Indra Prasetyo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
Abstract This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 117 officers. The objectives of this study are 1). To prove and analyze whether work experience and level of education simultaneously have a significant influence on the performance of health care workers at Dr. Slamet Martodhirdjo Pamekasan Regency. 2.) To prove and analyze whether work experience has a significant effect on the performance of health care workers at Dr. Slamet Martodhirdjo Pamekasan Regency. 3.) To prove and analyze whether the level of education has a significant effect on the performance of health care workers in Dr. Slamet Martodhirdjo Pamekasan Regency. The results showed that 1.) Work experience, level of education and professionalism simultaneously had a significant influence on the performance of health care workers at Dr. Slamet Martodhirdjo, Pamekasan Regency, the truth is proven and the hypothesis is accepted. 2.) Work experience has a significant influence on the performance of health care workers at Dr. Slamet Martodhirdjo Pamekasan Regency. 3.) The level of education has a significant influence on the performance of health care workers in Dr. Slamet Martodhirdjo Pamekasan Regency.